2000
DOI: 10.1128/aem.66.9.3945-3950.2000
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Gene Encoding Xanthan Lyase of Paenibacillus alginolyticus Strain XL-1

Abstract: Xanthan-modifying enzymes are powerful tools in studying structure-function relationships of this polysaccharide. One of these modifying enzymes is xanthan lyase, which removes the terminal side chain residue of xanthan. In this paper, the cloning and sequencing of the first xanthan lyase-encoding gene is described, i.e., the xalA gene, encoding pyruvated mannose-specific xanthan lyase of Paenibacillus alginolyticus XL-1. The xalA gene encoded a 100,823-Da protein, including a 36-amino-acid signal sequence. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 17 publications
(13 reference statements)
1
12
0
Order By: Relevance
“…Moreover, the larger amount of FOS and the sourdough technology stimulated the biosynthesis of dextran by selected LAB strains employed as starters. Recently, it was demonstrated that EPSs have a prebiotic effect on the human intestinal microbiota (14,16,(48)(49)(50). Furthermore, Olano-Martin et al (17) have shown by in vitro studies that dextran is a good substrate for butyric acid production by intestinal microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the larger amount of FOS and the sourdough technology stimulated the biosynthesis of dextran by selected LAB strains employed as starters. Recently, it was demonstrated that EPSs have a prebiotic effect on the human intestinal microbiota (14,16,(48)(49)(50). Furthermore, Olano-Martin et al (17) have shown by in vitro studies that dextran is a good substrate for butyric acid production by intestinal microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…strain GL1 is quite different from that in P. alginolyticus strain XL-1, since the posttranslational processing observed in Bacillus sp. strain GL1 has not occurred in P. alginolyticus strain XL-1 (34).…”
Section: Discussionmentioning
confidence: 99%
“…After submission of this article, results on the xanthan lyase gene (xalA) of Paenibacillus alginolyticus strain XL-1 were reported by Ruijssenaars et al (34). The xalA gene codes for a polypeptide consisting of 936 amino acid residues with a molecular weight of 100,823, including a signal sequence of 36 amino acid residues.…”
Section: Discussionmentioning
confidence: 99%
“…The variant xanthan with the truncated side chain could be produced by X. campestris mutants [ 7 , 10 ], whereas its production level is far from what is required for practical use [ 11 ]. Therefore, because of the molecular design of xanthan, the use of relevant enzymes seems to be a preferable and promising way to obtain a tailor-made xanthan with specific and desired properties [ 12 ]. Differing from other polysaccharide lyases acting on the polysaccharide backbone, xanthan lyase could cleave the linkage between the terminal mannosyl and the glucuronyl residues on the side chain by a β -elimination reaction, introducing a double bond between C4 and C5 of the uronosyl residue and subsequently might be exploited for further chemical modification [ 13 ].…”
Section: Introductionmentioning
confidence: 99%